Genomic instability in early systemic sclerosis. Issue 131 (July 2022) - Gniadecki, Robert; Iyer, Aishwarya; Hennessey, Dylan; Khan, Lamia; O'Keefe, Sandra; Redmond, Desiree; Storek, Jan; Durand, Caylib; Cohen-Tervaert, Jan Willem; Osman, Mohammed
Abstract: Objectives: Systemic sclerosis (SSc) is associated with secondary malignancies. Previous studies have suggested that mutated cancer proteins, such as RNA polymerase III, are autoantigens promoting an inflammatory response in SSc. However, it has never been previously investigated whether non-neoplastic tissue in SSc harbors mutations which may play a role in SSc pathogenesis. Methods: Skin biopsies were obtained from 8 sequential patients with a progressive form of early stage SSc (with severe skin and/or lung involvement). Areas of dermal fibrosis were microdissected and analyzed with deep, whole exome sequencing. Gene mutation patterns were compared to autologous buccal mucosal cells as a control. Results: SSc skin biopsies were hypermutated with an average of 58 mutations/10 6 base pairs. The mutational pattern in all samples exhibited a clock-like signature, which is ubiquitous in cancers and in senescent cells. Of the 1997 genes we identified which were mutated in at least two SSc patients, 39 genes represented cancer drivers (i.e. tumor suppressor genes or oncogenes) which are commonly found in gynecological, squamous and gastrointestinal cancer signatures. Of all the mutations, the most common mutated genes were important in regulating pathways related to epigenetic histone modifications, DNA repair and genome integrity. Conclusions: Somatic hypermutation occurs in fibrotic skin in patients with early progressive SSc. Cancer driver gene mutations may potentially play a fundamental role in the pathogenesis of SSc. Highlights: Non-synonymous genomic mutations are common in the dermis of patients with early systemic sclerosis. Genomic mutations have a clock-like signature, which is commonly present in cancer. Many mutated genes are important in the maintenance of genomic integrity.